Cancer invasion and metastasis: Insights from murine pubertal mammary gland morphogenesis - Githaka, John Maringa; Pirayeshfard, Leila; Goping, Ing Swie (Biochimica et biophysica acta. General subjects, 2023)
Cancer invasion and metastasis accounts for the majority of cancer related mortality. A better understanding of the players that drive the aberrant invasion and migration of tumors cells will provide critical targets to inhibit metastasis. Postnatal pubertal mammary gland morphogenesis is characterized by highly proliferative, invasive, and migratory normal epithelial cells. Identifying the molecular regulators of pubertal gland development is a promising strategy since tumorigenesis and metastasis is postulated to be a consequence of aberrant reactivation of developmental stages. In this review, we summarize the pubertal morphogenesis regulators that are involved in cancer metastasis and revisit pubertal mammary gland transcriptome profiling to uncover both known and unknown metastasis genes. Our updated list of pubertal morphogenesis regulators shows that most are implicated in invasion and metastasis. This review highlights molecular linkages between development and metastasis and provides a guide for exploring novel metastatic drivers. •Additional molecular targets are needed to combat tumor invasion and metastasis.•Developmental biology can provide novel insights in cancer invasion and metastasis.•Developmental motility genes are aberrantly hijacked by metastatic tumors.•List of potential therapeutic targets for cancer invasion and metastasis.•Transcriptomic gene signature for the Terminal End Bud of pubertal mammary gland.